Follow‐up of the Schmallenberg Virus Seroprevalence in Belgian Cattle. Issue 5 (12th December 2013) - Méroc, E.; Poskin, A.; Van Loo, H.; Van Driessche, E.; Czaplicki, G.; Quinet, C.; Riocreux, F.; De Regge, N.; Caij, B.; van den Berg, T.; Hooyberghs, J.; Van der Stede, Y.
Summary Schmallenberg virus (SBV), which emerged in Northwestern Europe in 2011, is an arthropod‐borne virus affecting primarily ruminants. Based on the results of two cross‐sectional studies conducted in the Belgian ruminant population during winter 2011–2012, we concluded that at the end of 2011, almost the whole population had already been infected by SBV. A second cross‐sectional serological study was conducted in the Belgian cattle population during winter 2012–2013 to examine the situation after the 2012 transmission period and to analyse the change in immunity after 1 year. A total of 7130 blood samples collected between 1st January and 28 February 2013 in 188 herds were tested for the presence of SBV‐specific antibodies. All sampled herds tested positive and within‐herd seroprevalence was estimated at 65.66% (95% CI: 62.28–69.04). A statistically significant decrease was observed between the beginning and the end of 2012. On the other hand, age‐cohort‐specific seroprevalence stayed stable from 1 year to the other. During winter 2012–2013, calves between 6 and 12 months had a seroprevalence of 20.59% (95% CI: 15.34–25.83), which seems to be an indication that SBV was still circulating at least in some parts of Belgium during summer–early autumn 2012. Results showed that the level of immunity against SBV of the animals infected has not decreased and remained high after 1 year and that the spread of the virus has slowed down considerably during 2012. This study also indicated that in the coming years, there are likely to be age cohorts of unprotected animals.